2023
DOI: 10.3390/jpm13030501
|View full text |Cite
|
Sign up to set email alerts
|

Association of HTTLPR, BDNF, and FTO Genetic Variants with Completed Suicide in Slovakia

Abstract: Since suicide and suicidal behavior are considered highly heritable phenotypes, the identification of genetic markers that can predict suicide risk is a clinically important topic. Several genes studied for possible associations between genetic polymorphisms and suicidal behaviors had mostly inconsistent and contradictory findings. The aim of this case-control study was to evaluate the associations between completed suicide and polymorphisms in genes BDNF (rs6265, rs962369), SLC6A4 (5-HTTLPR), and FTO (rs99396… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Suicidal ideation and completed suicide can occur in both one-episode and recurrent depression, but the risk is generally considered higher in individuals with recurrent depression due to the chronic and repetitive nature of their condition. Our recently published study [ 26 ] demonstrated a significant association between rs962369 and completed suicide. Based on our findings, we hypothesize that rs962369 is one of the risk factors that contribute to the development of recurrent MDD and may ultimately lead to completed suicide.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Suicidal ideation and completed suicide can occur in both one-episode and recurrent depression, but the risk is generally considered higher in individuals with recurrent depression due to the chronic and repetitive nature of their condition. Our recently published study [ 26 ] demonstrated a significant association between rs962369 and completed suicide. Based on our findings, we hypothesize that rs962369 is one of the risk factors that contribute to the development of recurrent MDD and may ultimately lead to completed suicide.…”
Section: Discussionmentioning
confidence: 99%
“…The BDNF gene is located on chromosome 11p14.1 in humans, and it harbors a specific single nucleotide polymorphism (SNP) known as rs6265 C>T. This change results in the substitution of valine with methionine at the 66th codon (Val66Met) of the BDNF precursor, known as pro-BDNF. This substitution leads to a reduction in the secretion of the BDNF protein [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Genotyping of the FTO rs9939609 and BDNF (rs6265, rs962369) polymorphisms was performed by high-resolution melting analysis in the presence of an unlabeled probe [37]. The SLC6A4 (5-HTTLPR) gene variants were analyzed by gel electrophoresis after a polymerase chain reaction [38].…”
Section: Genotypingmentioning
confidence: 99%